COMPARISON OF LATVIAN QUALIFIED BASKETBALL AND HANDBALL PLAYERS PERFORMANCE - Pontaga, Inese; Zidens, Janis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of our investigation was to compare qualified basketball and handball players’ anthropometric and performance (aerobic and anaerobic endurance, explosive power) characteristics. Male handball and basketball players from Premium league teams voluntary participated. The aerobic endurance was measured on a treadmill, the intensity of running increased step by step, the test was performed to exhaustion. The oxygen uptake, heart rate and running speed were measured. The lactate concentration was detected in periphery blood samples by special strips in the end of every load step and after the test. Maximal vertical jump heights of the counter-movement jump with hands on the hips and the free jump with motions of arms were measured on a special device. The height of basketball players is higher in comparison with handball players (p=0.002), but the body weight and body mass index did not differed significantly (p>0.05). The aerobic endurance characteristics (heart rate and oxygen uptake at the anaerobic threshold load intensity, and maximal oxygen uptake) were greater in basketball than in handball players (p<0.04). The maximal lactate concentration in blood plasma two minutes after the test was higher in handball players than in basketball players (p=0.043). The vertical jump heights are the same in basketball and handball players (p>0.05).